To solve the given problems, we need to perform function composition.
(a) For \((f \circ g)(x)\), substitute \(g(x)\) into \(f(x)\).
(b) For \((g \circ f)(x)\), substitute \(f(x)\) into \(g(x)\).
(c) For \((f \circ f)(x)\), substitute \(f(x)\) into itself.
We are given two functions:
We need to calculate the compositions:
The composition \( (f \circ g)(x) \) means we substitute \( g(x) \) into \( f(x) \).
Substitute \( g(x) = x - 3 \) into \( f(x) \): \[ f(g(x)) = f(x - 3) = (x - 3)^2 - 7(x - 3) \]
Expand \( (x - 3)^2 \): \[ (x - 3)^2 = x^2 - 6x + 9 \]
Substitute back into the expression: \[ f(x - 3) = x^2 - 6x + 9 - 7(x - 3) \]
Distribute the \(-7\): \[ -7(x - 3) = -7x + 21 \]
Combine like terms: \[ f(x - 3) = x^2 - 6x + 9 - 7x + 21 = x^2 - 13x + 30 \]
The composition \( (g \circ f)(x) \) means we substitute \( f(x) \) into \( g(x) \).
Substitute \( f(x) = x^2 - 7x \) into \( g(x) \): \[ g(f(x)) = g(x^2 - 7x) = (x^2 - 7x) - 3 \]
Simplify the expression: \[ g(f(x)) = x^2 - 7x - 3 \]
The composition \( (f \circ f)(x) \) means we substitute \( f(x) \) into itself.
Substitute \( f(x) = x^2 - 7x \) into \( f(x) \): \[ f(f(x)) = f(x^2 - 7x) = (x^2 - 7x)^2 - 7(x^2 - 7x) \]
Expand \( (x^2 - 7x)^2 \): \[ (x^2 - 7x)^2 = x^4 - 14x^3 + 49x^2 \]
Distribute the \(-7\): \[ -7(x^2 - 7x) = -7x^2 + 49x \]
Combine like terms: \[ f(f(x)) = x^4 - 14x^3 + 49x^2 - 7x^2 + 49x = x^4 - 14x^3 + 42x^2 + 49x \]
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.